Phytohemagglutinin-Induced Mitotic Index in Blood Lymphocytes: A Potential Biomarker for Breast Cancer Risk - Kosti, Ourania (Libertas Academica, 2010)
BACKGROUND: Cell proliferation is associated with the pathogenesis of cancer because it provides opportunities for accumulating genetic mutations. However, biomarkers of cell proliferation in response to environmental stimuli have not been adequately explored for breast cancer risk. METHODS: In a case-control study of 200 breast cancer patients and 360 healthy controls, we investigated the association between phytohemagglutinin (PHA)-induced mitotic index in blood lymphocyte and breast cancer risk. RESULTS: Having high mitotic index (>3.19%) was associated with an increased risk of breast cancer, with adjusted odds ratios (95% confidence interval) of 1.54 (1.03–2.30) and 2.03 (1.18–3.57) for all women and post-menopausal women, respectively. Mitotic index was correlated with some reproductive factors and body mass index in controls. CONCLUSIONS: Our data suggest increased PHA-induced mitotic index in blood lymphocytes is associated with an increased breast cancer risk and that this association may be modulated by reproductive and other hormones.